IMPLEMENTASI PROGRAM KKN PENDIDIKAN DALAM PENGALAMAN KEMAMPUAN MENYIMAK SISWA KELAS III UPT SDN NO.78 BALANG MELALUI KUNJUNGAN KE RUMAH BACA PANGNGADAKKANG DESA BONTOKASSI KABUPATEN TAKALAR - Siti Nuramaliyah; Dea Ayuni; M. Akhyar Armar; Nasrun; Ratnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Listening is one of the fundamental skills in Indonesian language learning at the elementary school level, yet it often receives less attention compared to other language skills. This study aims to describe the implementation of the Community-Based Education Program (KKN Pendidikan) in improving the listening skills of third-grade students at UPT SDN No.78 Balang through a learning visit to the Pangngadakkang Reading House in Bontokassi Village, Takalar Regency. A descriptive qualitative approach was employed, involving 31 student participants. The learning activities were designed contextually by integrating storytelling, group discussions, read-aloud sessions, and active listening exercises in a non-formal learning environment. The results indicated a significant improvement in students' focus, participation, and comprehension during listening activities. The interactive and engaging atmosphere of the reading house proved to be an effective alternative learning space. Moreover, the strong collaboration between student-teachers, classroom teachers, and reading house facilitators played a vital role in the success of the program. These findings suggest that an environment-based literacy approach can be an effective strategy for enhancing listening skills among elementary school students.